PARENTING TECHNIQUE BASED ON THE SOCIAL LEARNING THEORY - Yunitasari, Septiyani Endang; Hufad, Achmad; Rakhmat, Cece; Soendari, Tjutju (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
The existing problem is the lack of parenting knowledge by parents with mild mental retardation children so that many mistakes in parenting are found, such as (1) mothers with mild mental retardation use approach by spoiling their children, (2) in providing guidance to their children, mothers with mild mental retardation do not employ task analysis, (3) mothers with mild mental retardation children do not apply guiding principles that can empower their children to own skills. The approach used in this study was a qualitative approach and descriptive method. The research subjects in this study were 5 (five) parents with mild mental retardation children who attend SLBN (Special Education School) Cileunyi. Based on the existing problems, the Social Learning Theory-based parenting technique for Mild Mental Retardation is implemented by (1) avoiding complex verbal commands, otherwise giving simple and concrete commands; (2) using media to explain the messages parents will convey; (3) using parenting techniques based on the behaviour of family members as role models; (4) providing motivation when children fail to imitate something; (5) giving praise or reward when the children succeed in performing tasks or imitate the model’s behaviour; (6) parenting aims to make children independent, thus it must be based on assessment; (7) If using media such as television, video, and so on, choosing videos that are simple, easy to understand, and easy to imitate by mental retardation children; (8) Repeating training the children so that it becomes a habit for them.